Basic Financial Management Education for Madrasah Students as Prospective Young Entrepreneurs - Cicely Delfina Harahap; Murtanto; Dyah Astarini; Lailatun Hasanah; Rahma Febriana (Mattawang: Jurnal Pengabdian Masyarakat, 2025)
This community service activity aims to enhance the understanding and skills of students at Madrasah Aliyah Negeri (MAN) 3 Jakarta in managing simple financial practices as a foundation for becoming independent and competitive young entrepreneurs. The main issue faced by students is the lack of understanding of basic financial management concepts for both personal and business purposes, such as expenditure planning, transaction recording, and cash flow control. The training was conducted by the lecturers of the Faculty of Economics and Business, Universitas Trisakti, on December 7, 2024, from 10:00 to 12:00 WIB, involving 23 participants. The method used was a participatory approach through counseling, interactive discussions, simple financial recording simulations, and exercises in preparing small business budgets. The results of the activity showed a significant improvement in students’ understanding of the importance of financial recording and capital management in entrepreneurial activities. Participants also became more motivated to plan their personal and business finances systematically using simple record-keeping formats based on Excel tables or manual cash books. This activity had a positive impact on improving financial literacy among madrasah students and fostering a rational and responsible entrepreneurial spirit. In the future, this program is expected to be developed into more practical follow-up training by integrating digital technology to support entrepreneurship learning within the madrasah environment.